Reaction of cassava's germoplasm to Xanthomonas axonopodis pv. manihots - Nery-Silva, Flavia Andrea; Fernandes, Jonas Jäger; Juliatti, Fernando César; Melo, Benjamim de (Semina: Ciências Agrárias, 2007)
The cassava is presented as an important stach source, mainly in the tropics. The bacteriosis disease caused by Xanthomonas axonopodis p.v. manihots is the most important disease of this culture and its damage can achieve 30% of the production, or even more. This work objectified to evaluate, in green house condition the reaction of "mandioca mansa" and the "mandioca brava" cassava's germoplasma to the two isolates of Xanthomonas axonopodis p.v. manihots. Trials were developed at the Instituto de Ciências Agrárias da Universidade Federal de Uberlândia. The plants had been inoculated by seasor's cuttings of three central leaflets in three completely opened new leaves, following by insertion of a little wood stick at the oldest leaf's axel, using a bacterial suspension at 2x109u.f.c. mL-1. The inoculation happened at the 42nd day after planting and the evaluation at the 41st day after inoculation. The evaluation criteria were: notes of visual symptoms in the aerial part, percentages defoliation and systemic infection of the stalk. The results showed the efficiency of the evaluation criteria applied at this work for the isolates virulence study. The Uberlândia isolate was more virulent to "mandioca mansa" cassava cultivars and the Lavras isolate was more virulent to "mandioca brava" cassava cultivars. That indicates the need of using isolates from the region where the germoplasm will be cultivated. Considering the germoplasm resistance reaction analysis, both the sistemic infection precentage and the defoliation criteria presented as very effective. Oustanding behavior was observed for the Vassoura, Amarela, Vermelha and Castelinho cultivars and for the CPAC88-11 clone.